2011
DOI: 10.5539/ass.v7n2p25
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Mobilisation Performance of Union Parishad in Bangladesh: Is It Convergence of Central-Local Relations?

Abstract: Despite several local revenue sources, Union Parishads (Councils) in Bangladesh are yet to perform optimal local revenue mobilisation. This paper evaluates Unions revenue trend and performance, budget and planning practices, effect of central grants on local revenue in the backdrop of central government recent initiative for Unions capacity building. Analysis includes three representative Unions, in a comparative perspective, and uses secondary and primary data (from Parishad functionaries, local citizen, gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A satisfactory number 4 of people participated in the local planning process. Like Ullah and Pongquan (2011), this study found that the new system of UP planning has been facilitating democratisation. People's access to these processes -WSs and OBMsis creating a pathway for mass participation in decision-making at the local level.…”
Section: Popular Participation Has Been Achievedmentioning
confidence: 64%
“…A satisfactory number 4 of people participated in the local planning process. Like Ullah and Pongquan (2011), this study found that the new system of UP planning has been facilitating democratisation. People's access to these processes -WSs and OBMsis creating a pathway for mass participation in decision-making at the local level.…”
Section: Popular Participation Has Been Achievedmentioning
confidence: 64%